Is a secondary currency essential? - On the welfare effects of a new currency - Max Fuchs; Jochen Michaelis (Journal of Economics and Statistics, 2023)
The coexistence of fiat money (cash) and digital monies constitutes a system of parallel currencies as media of exchange. This paper asks whether a new (digital) currency is essential: Does a new currency allow for a better resource allocation even if a fully accepted currency is in circulation and remains in circulation? Using the dual currency search model of Kiyotaki and Wright (1993. A search-theoretic approach to monetary economics. Am. Econ. Rev. 83: 63-77), we show how the introduction of a secondary currency affects average utility. There is some scope for a welfare improvement as the welfare effect depends on differences in returns and costs, and, in particular, on the proportion of cash traders who will be replaced by digital money traders.
Keywords: E41; E42; E51; 330; digital money; dual currency regime; welfare comparison